Inclusive practices in basic education - Carlos Guimarães Junior, Jose; Costa de Santana, Marttem; Carneiro Braga, Francisco; Carlos Triches, Jean; Ribeiro Gontijo , Fabrícia; de Oliveira, Hellyegenes; Lima Costa e Silva, Savio; Bueno Vieira, Fernando; Davi Ferreira Dos Santos, Jefferson (Seven Editora, 2023)
Currently, the educational system needs to give special attention to pedagogical practices, transforming the learning process into an inclusive process and always respecting diversity, without forgetting that the role of a modern school should be assist in the cognitive, emotional and social development of the child, development with the objective of promoting it to transform it into a full-fledged citizen. The inclusion of children with special needs is the focus of this research, since not all subjects involved in early childhood education are prepared to perform the specifically indicated inclusion. This study is a case study on inclusive education for children with special needs, which through the bibliographic method, will bring the demonstration of the importance of an inclusive early childhood education. According to Article 205 of the Brazilian Federal Constitution of 1988, education is a universal right subject to government control. Since then, numerous initiatives have been established at the national and local level to ensure that people with intellectual disabilities, a high level of skill or gifted access have access to ordinary schools for instruction, where they can acquire knowledge over time. The aim of this study is to criticize the way Brazil is implementing the national laws that govern special education, outlineing the tensions, challenges and opportunities that arise throughout this process. DOI: https://doi.org/10.56238/tfisdwv1-026